Biochemical–molecular–genetic biomarkers in the tear film, aqueous humor, and blood of primary open-angle glaucoma patients - Pinazo-Durán, Maria D.; Zanón-Moreno, Vicente; García–Villanueva, Carolina; Martucci, Alessio; Peris-Martínez, Cristina; Vila-Arteaga, Jorge; García-Medina, Jose J.; Andrés–Blasco, Irene; Gallego–Martínez, Alex; Nucci, Carlo; García–Feijoo, Julian (Frontiers in Medicine, 2023)
Glaucoma is a chronic neurodegenerative disease accounting for the first irreversible cause of blindness worldwide. Clinical and molecular glaucoma biomarkers indicate the biological state of the visual system, as a response to the elevated intraocular pressure. Classical and uncovering novel biomarkers of glaucoma development and progression, follow-up, and monitoring the response to treatment, are pivotal objectives to improve vision outcomes. While the glaucoma imaging field has been successful in validating biomarkers of disease progression, there is still a huge lack in developing new biomarkers of early glaucoma, at the preclinical and initial glaucoma stages. Outstanding clinical trials and animal models study designs, the use of innovative technology, and analytical approaches in bioinformatics, are essential tools to successfully uncovering novel glaucoma biomarkers, with a high potential for translation into the clinical practice. To better understand the clinical and biochemical-molecular-genetic glaucoma pathogenesis, we conducted an analytical, observational, case-comparative/control study in 358 primary open-angle glaucoma (POAG) patients and 226 comparative-control individuals to collect tears, aqueous humor and blood, to be processed for identifying POAG biomarkers by exploring several biological pathways, such as inflammation, neurotransmitter/neurotrophin alteration, oxidative stress, gene expression, miRNAs fingerprint and its biological targets, and vascular endothelial dysfunction. We are especially enthusiastic to gather as much information as possible on POAG biomarkers, to learn how these can be used to better steer the diagnosis and therapy of glaucoma to prevent blindness, in the foreseeable future.